Coffee wilt disease: The forgotten threat to coffee - Peck, Lily D; Boa, Eric (Wiley Subscription Services, Inc, 2024)
AbstractCoffee is attacked by several highly damaging pests and diseases, which include cof-fee wilt disease (CWD). Despite a devastating impact in recent years, CWD receives little attention and its importance is downplayed or simply ignored. Memories are short and knowledge of past outbreaks fragmentary. Nearly two decades after the last major outbreaks, CWD has quietly faded into the background. This review de-scribes a series of outbreaks of CWD across Africa, from Uganda to Guinea, from the first discovery in the 1920s to a hugely damaging recurrence that began in the 1970s and lasted through to the 2000s. This second wave had devastating impacts on grow-ers and communities in the Democratic Republic of Congo and in Uganda. This review examines the origins of the disease, how and why it spread, and attempts to manage the outbreaks. Recent work on new pathogen variants is also considered. This review aims to recount these events and to evaluate the strategic successes and failures at national, regional and international levels in tackling the second wave of CWD
Keywords: Fusarium xylarioides, robusta and arabica coffee